2008
DOI: 10.1016/j.tmaid.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic radiation in commercial aviation

Abstract: This paper reviews the current knowledge of cosmic radiation and its applicability to commercial aviation. Galactic cosmic radiation emanates from outside the solar system, while occasionally a disturbance in the sun's atmosphere leads to a surge in radiation particles. Protection is provided by the sun's magnetic field, the earth's magnetic field, and the earth's atmosphere. Dose rates are dependent on the altitude, the geomagnetic latitude and the solar cycle. For occupational exposure to ionising radiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Specifically, USAF pilots accrue fewer flying hours and fly at lower altitudes compared with long-haul commercial aircrew. The latter flights are not only of longer duration but may also include polar routes, which yield higher cosmic radiation exposure (1). Indeed, the study by Pukkala (9) found an increased relative risk for prostate cancer in long-haul pilots: 3.88 for aviators with >10,000 hours compared with pilots with <5,000 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, USAF pilots accrue fewer flying hours and fly at lower altitudes compared with long-haul commercial aircrew. The latter flights are not only of longer duration but may also include polar routes, which yield higher cosmic radiation exposure (1). Indeed, the study by Pukkala (9) found an increased relative risk for prostate cancer in long-haul pilots: 3.88 for aviators with >10,000 hours compared with pilots with <5,000 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this is that the total effective dose rate (μSv h −1 ) at 30 000 ft is 90 times the sea-level value. 9 This increases to 180 times the sea level value at 40 000 ft and then to 360 times at 65 000 ft. Passengers fl ying at twice the speed of a subsonic vehicle will be exposed for half the time.…”
Section: 83 )mentioning
confidence: 94%
“…Studies have been carried out to determine the health risks of airline crews to cosmic ray exposures at typical flight altitudes (Bagshaw, 2014). EPCARD, one of the computer packages developed on behalf of the European commission used in these studies is based on the FLUKA transport code, which was developed to carry out detailed simulations for particle physics detectors.…”
Section: Other Cosmic Ray Applicationsmentioning
confidence: 99%